Outer Membrane Vesicles Derived From Escherichia coli Regulate Neutrophil Migration by Induction of Endothelial IL-8 - Lee, Jaewook; Yoon, Yae Jin; Kim, Ji Hyun; Dinh, Nhung Thi Hong; Go, Gyeongyun; Tae, Sookil; Park, Kyong-Su; Park, Hyun Taek; Lee, Changjin; Roh, Tae-Young; Di Vizio, Dolores; Gho, Yong Song (Frontiers in Microbiology, 2018)
Outer membrane vesicles (OMVs) are spherical, proteolipid nanostructures that are constitutively released by Gram-negative bacteria including Escherichia coli. Although it has been shown that administration of E. coli OMVs stimulates a strong pulmonary inflammatory response with infiltration of neutrophils into the lungs in vivo, the mechanism of E. coli OMV-mediated neutrophil recruitment is poorly characterized. In this study, we observed significant infiltration of neutrophils into the mouse lung tissues in vivo, with increased expression of the neutrophil chemoattractant CXCL1, a murine functional homolog of human IL-8, on intraperitoneal administration of E. coli OMVs. In addition, OMVs and CD31-positive endothelial cells colocalized in the mouse lungs. Moreover, in vitro results showed that E. coli OMVs significantly increased IL-8 release from human microvascular endothelial cells and toll-like receptor (TLR)4 was found to be the main component for recognizing E. coli OMVs among human endothelial cell-associated TLRs. Furthermore, the transmigration of neutrophils was suppressed in the lung tissues obtained from TLR4 knockout mice treated with E. coli OMVs. Taken together, our data demonstrated that E. coli OMVs potently recruit neutrophils into the lung via the release of IL-8/CXCL1 from endothelial cells in TLR4- and NF-κB-dependent manners.